HUBUNGAN ANTARA MUSYAWARAH DAN PEMERINTAHAN - Lailatul Rif’ah (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: Deliberation is ordered in the Al Quran and the hadith. However, when the Koran talks about deliberation, it does not specify which forms of deliberation are most appropriate. The Prophet also carried out deliberations in different forms and ways depending on the atmosphere surrounding him. It can also be understood, that the pattern and form of Deliberation implementation depends on conditions in accordance with the cultural and social development of society, especially in the state government. Deliberation provides solutions and educates individuals to have a spirit of grace and responsibility in both vertical and horizontal relationships. Measure and control emotions and become knowledge for discussion partners.Keyword: Deliberation and Government